ASAL USUL DAN MAKNA NAMA GELAR DATUAK DI NAGARI NAN TUJUAH KECAMATAN PALUPUH KABUPATEN AGAM - Amrizal Amrizal (Jurnal Elektronik WACANA ETNIK, 2011)
This study reviews the meaning of datuak title as an elder (penghulu) in Nagari Nan Tujuah, Palupuh Agam which based on the traditional proverb "ketek banamo, gadang bagala". This research use qualitative method with interview techniques and semiotic theory by Michael Riffaterre. The results shows datuak titles in MInangkabaukabau, especially those in Nagari Nan Tujuah depart from an idea and a good hope. With this title, the elders are expected will fulfill their duties and functions as the people will.